A study on structure and functions of organs involved in the formation of Mongolian Khuumii sound - Tsagaankhuu, Rentsendorj; Sundui, Enebish; Bold, Juramt; Shuumarjav, Uurtuya; Palamdorj, Ganchimeg; Luvsandagva, Byambasuren; Tsagaankhuu, Dorjsuren; Tsevegmid, Erdembileg; Dorjkhuu, Amgalanbaatar; Bodi, Dagdanbazar; Dagdanbazar, Nyamdorj (Proceedings of the Mongolian Academy of Sciences, 2020)
Khuumii (throat or overtone singing) is a unique form of art derived from the nomadic population of Central Asia, which is a type of singing in which the singer manipulates the resonances (or formants) created as air travels from the lungs, past the vocal folds, and out of the lips to produce a melody. A total of 60 participants, aged 18-60 years (54 men and 6 women), were selected by non-random sampling method using cross-sectional study. X-ray, endoscopy, and sound research method were used in the study, and the composition of blood gas was analysed. X-ray examination determined the state during each different types of Khuumii; Shakhaa and Kharkhiraa. As the basic timbre of Shakhaa Khuumii went up progressively the larynx grew and the compression strength increased, while the basic timbre went down, and the larynx became lower. In the case of Kharkhiraa Khuumii, the larynx position was elevated to a relatively small extent compared to Shakhaa Khuumii and the distance between the sublingual bone and the larynx was large. The sublingual bone trunk lowered during Shakhaa Khuumii, while it was slightly elevated during Kharkhiraa Khuumii. The laryngeal endoscopy evaluated the movement of true and false vocal chords, glottal volume, movements of epiglottis and arytenoid cartilage, and mucosa. Furthermore, the sound frequency is 2-4 times higher than that of normal speech, and sound volume is 0.5-1 times higher. The blood gas composition test showed partial pressure (pO2), and saturation of oxygen (SaO2) decreased after performing Khuumii. In the case of Shakhaa and Kharkhiraa Khuumi, it is appropriate to divide Khuumii into two main types according to structural and functional changes in the organs involved.